Adolescent exposure to cannabis marketing following recreational cannabis legalization in Canada: A pilot study using ecological momentary assessment. (December 2021) - Noël, Chelsea; Armiento, Christopher; Péfoyo, Anna Koné; Klein, Rupert; Bédard, Michel; Scharf, Deborah
Highlights: Cannabis advertising reaches adolescents. Ecological momentary assessment (EMA) captures adolescent exposure to cannabis ads. EMA can be used to assess cannabis advertising policies designed to protect youth. Abstract: Objective: The goal of this pilot study was to assess the feasibility of a 9-day, smartphone-based ecological momentary assessment (EMA) protocol for tracking the frequency of Canadian adolescents' exposures to cannabis marketing, their reactions to such exposures, and the context in which exposures occur in the real-world and in real-time. Method: Participants were n = 18 adolescents between the ages of 14 and 18 years of age. They used an EMA application to capture and describe cannabis marketing exposures through photographs and brief questionnaires assessing marketing channel and context. Participants also rated their reactions to each exposure in real-time. Results: Results showed that participants were generally compliant with the protocol. Participants recorded 40 total exposures to cannabis marketing, representing an average of 2.2 ( SD 2.3) exposures per participant during the 9-day study. Exposures tended to occur in the afternoon (45.0%) or evening (37.5%), and while participants were at home (70%) and alone (52.5%). Most exposures occurred through promotion by public figures (27.5%) or explicitly marked internet ads (27.5%). Conclusion: This is the first study to demonstrate the feasibility and utility of EMA to capture adolescent exposures to cannabis marketing as it occurs in participants' natural environments. Our research offers an early look at the predictable wave of cannabis advertising targeting youth and a promising approach for studying its impacts in a post-legalization context, as well as a strategy for assessing policies, such as advertising restrictions, intending to mitigate the harms of early cannabis use among youth.